2020
DOI: 10.1063/1.5129946
|View full text |Cite
|
Sign up to set email alerts
|

Strong-field control of H3+ production from methanol dications: Selecting between local and extended formation mechanisms

Abstract: Using the CD3OH isotopologue of methanol, the ratio of D2H+ to D3+ formation is manipulated by changing the characteristics of the intense femtosecond laser pulse. Detection of D2H+ indicates a formation process involving two hydrogen atoms from the methyl side of the molecule and a proton from the hydroxyl side, while detection of D3+ indicates local formation involving only the methyl group. Both mechanisms are thought to involve a neutral D2 moiety. An adaptive control strategy that employs image-based feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 96 publications
2
20
1
Order By: Relevance
“…As a consequence of the displacement of hydrogen atoms, significant structural rearrangements could be triggered, leading to isomerization and thus alter the chemical functions of those molecules. In particular, for the ionic organic molecules, numerous studies have been conducted to elucidate the formation and evolution of ultrafast hydrogen migration through the sophisticated momentum imaging techniques [5][6][7][8][9][10][11][12][13][14][15][16][17] . It has been found that the hydrogen-migration channel can dominate over direct fragmentation in molecular cations 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of the displacement of hydrogen atoms, significant structural rearrangements could be triggered, leading to isomerization and thus alter the chemical functions of those molecules. In particular, for the ionic organic molecules, numerous studies have been conducted to elucidate the formation and evolution of ultrafast hydrogen migration through the sophisticated momentum imaging techniques [5][6][7][8][9][10][11][12][13][14][15][16][17] . It has been found that the hydrogen-migration channel can dominate over direct fragmentation in molecular cations 5 .…”
mentioning
confidence: 99%
“…In addition to the well-known single hydrogen migration, another more complicated process, that is, the double hydrogen migration has been proven to play a more important role than generally assumed in molecular fragmentation 6 . Furthermore, in some of those hydrogen-migration studies special attention has been paid to the reaction dynamics in the course of H 3 + formation [12][13][14][15][16][17] . H 3 + has been brought into research focus by its unique structural and dynamical nature and astronomical significance as the most important interstellar medium 18,19 .…”
mentioning
confidence: 99%
“…The experimental techniques applied in this study have recently been discussed elsewhere [21,36], and in this section we will only highlight a few key points. Two different approaches are used to examine the interactions of intense laser pulses with ethane gas: First, the laser pulses are shaped using an acousto-optic programmable dispersive filter (AOPDF) [37] and the ethane reaction products are measured using velocity map imaging (VMI) [38,39].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The intramolecular migration of hydrogen continues to be an active area of investigation in ultrafast science [1][2][3][4][5][6][7][8][9][10][11] with implications for topics ranging from combustion [12] to peptide dissociation [13] and characterizing conformational differences in molecules [14,15]. In some cases the migration of hydrogen leads to the formation of new molecular ions, such as H + 3 [5,[16][17][18][19][20][21], by processes such as H 2 roaming or double hydrogen migration [18,19,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation